Impulsivity and affect reactivity prospectively predict disordered eating attitudes in adolescents: A 6-year longitudinal study - Evans, Brittney C. (Eur Child Adolesc Psychiatry, 2019)
INTRODUCTION. Eating disorders (EDs) are associated with significant psychological and physical comorbidities, and adolescence is a particularly high-risk time for the development of EDs. Impulsivity (i.e., acting with little conscious judgment or forethought) and affect reactivity (i.e., changes in negative affect in response to a stressor) are hypothesized to contribute to the development of binge/purge ED pathology. The current study is the first to examine the prospective relationships between impulsivity and affect reactivity as predictors of the development of ED-attitudes in adolescents over time. METHODS. 206 adolescents participated in a longitudinal study examining the development of psychopathology. ED-attitudes were assessed via the College Eating Disorders Screen (COEDS) annually for 6 years. Baseline impulsivity and affect reactivity were also assessed. Affect reactivity, impulsivity, and their interaction were examined as baseline predictors of changes in ED-attitudes over time using latent growth modeling. RESULTS. Results of latent growth modeling indicated that ED-attitudes increased over time. The interaction between impulsivity and affect reactivity significantly predicted the slope of ED-attitudes, such that the relationship between impulsivity and ED-attitudes was strongest for those with elevated levels of affect reactivity. DISCUSSION. Findings suggest that greater levels of affect reactivity and impulsivity are key risk factors for the development of ED-attitudes in adolescents. Subsequent research should examine the relation between affect reactivity and impulsivity in predicting objectively measured ED-behaviors, in addition to ED-attitudes. Further investigation may implicate affect reactivity and impulsivity as important targets for early intervention to prevent onset of ED symptoms in adolescents.